KAJIAN FILSAFAT HUKUM TENTANG PEMBENTUKAN PERATURAN DAERAH - Victor Juzuf Sedubun (Faculty of Law, Universitas Pattimura, 2010)
Establishment of regulations in the area causing problems when the rule is applied. Some parties feel that the rules are there to organize and manage the region carried out only for the interests of certain groups. The fact that there are not any products that regulation can work well because the cause of conflict in society. Resulting in the cancellation of a regional regulation.